The Predictive Value of Baseline Target Lesion SYNTAX Score for No-Reflow during Urgent Percutaneous Coronary Intervention in Acute Myocardial Infarction - Guofeng Gao; Han Xu; Dong Zhang; Chenxi Song; Changdong Guan; Bo Xu; Dong Yin; Kefei Dou (Journal of Interventional Cardiology)
Objectives. To evaluate the predictive value of target lesion SYNTAX score (TL-SS) for no-reflow in the patients with acute myocardial infarction undergoing urgent percutaneous coronary intervention (PCI). Background. Risk assessment, prevention, and prompt management of no-reflow in urgent PCI are crucial but remain challenging. SYNTAX score emerged as a tool for prediction, but may contain redundant information. Methods. After screening of consecutive patients who underwent urgent PCI in Fuwai Hospital from January 2013 to December 2013, 487 patients with 528 lesions were involved. The endpoint was no-reflow during the PCI procedure. Results. No-reflow occurred in 52 patients (10.7%) and 53 lesions (10.0%). High TL-SS levels were strongly associated with increased risks of no-reflow in the urgent PCI procedure (all adjusted P<0.05). TL-SS displayed good discrimination ability for no-reflow (C-statistics = 0.76, 95% CI 0.72–0.80), which was better than that of SYNTAX score (P=0.016). Following categorizing the lesions into two groups according to the Youden Index, the high-risk group (TL-SS ≥8) showed significantly higher no-reflow rate compared with the low-risk group (TL-SS <8) (20.6% vs. 3.6%, odds ratio 6.86, 95% confidence interval 3.50–13.41, P<0.001). In the target lesions that underwent balloon predilation, maximum predilation pressure >10 atm was associated with higher rate of no-reflow in the high-risk group (odds ratio 3.81, 95% confidence interval 1.10–13.17). Conclusions. TL-SS is a potential predictor for risk stratification of no-reflow in urgent PCI. In the high TL-SS lesions that underwent balloon predilation, maximum predilation pressure >10 atm was associated with higher risk of no-reflow.